KARAKTERISTIK DAN SIKAP PEDULI LINGKUNGAN MASYARAKAT PESISIR KAWASAN CILINCING DKI JAKARTA - Anna Rejeki Simbolon (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
Cilincing area is one area with high anthropogenic activity. As one of the industrial area, this area stands several companies and factories. Cilincing area is one of the port areas of merchant ships both from within and outside the country and shelter in Kawasan Berikat Nusantara (KBN). In addition, Cilincing Area is an estuary or coastal area, so it becomes the center of port and aquaculture. In this area there is a Cilincing Fishing Place (TPI Cilincing) which became the center of fish sales in this area. Density of population activity in this area has not been accompanied by the attitude of society who care about the environment. The purpose of this research are: (1) to know the characteristic of society in Cilincing Area of ​​Coastal of DKI Jakarta; and (2) to know the picture of environmental care attitude toward coastal community in Cilincing Area of ​​PKI Jakarta. Results and conclusions from this study indicate the characteristics of Cilincing Area community, among others aged 35-45 years, with a length of stay 0-10 years. The public is generally educated elementary-high school with a job as a fisherman. The dominant sex is male and comes from the island of Java. Cilincing community is still dominated by unfavorable attitude. Keywords: Cilincing area, environmental concern, characteristics humans